Upaya Peningkatan Kualitas Mahasiswa Melalui Program Magang Bersertifikat Kampus Merdeka (Studi Kasus Ombudsman Republik Indonesia) - Febry Renaldi; Reza Rizkynata; Muhammad Khoirul Anwar; Nurlita Purnama; Annisa Miskiyah (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
Efforts have been made to improve the quality of students through an apprenticeship program from the Merdeka Learning Campus policy which can be used as a forum for all students at Indonesian state and private universities to develop competencies in various fields of interest. Before accepting a job and carrying out the various programs that will be provided, all apprentices are given briefing in advance by each apprentice partner. The briefing received is in the form of a more in-depth explanation of the intended internship location so that all apprentices get a more in-depth picture of the main tasks and functions of each work unit they will choose later. After that, all apprentices chose the work unit to go to and were introduced to the person in charge of each work unit to be followed up afterwards. The certified apprenticeship program aims to improve the quality and competency capacity of students through work and programs provided by apprentice partners during this Certified Internship activity. Apart from that, through this activity it is hoped that students can re-sharpen their hard skills and soft skills so that they are able to compete when pursuing their careers in this globalization era.